Data dissemination and effective Path Management on Wireless Sensor Network (International Journal of Engineering and Computer Science, 2014)
Energy efficiency is very important in wireless sensor network. When data is transmitted through WSN then Ant based algorithm is followed. Also same data may be transmitted multiple times. In order to solve the problem Selective data transmission can be followed. We here suggest Range based algorithm rather than Ant based algorithm. In Ant based algorithm major stress is toward identifying the validity of path but the method involved, utilize too much energy and resources. In range based algorithm concept of signal strength will be used.